2017
DOI: 10.1557/jmr.2017.319
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural evolution and functional fatigue of a Ti–25Ta high-temperature shape memory alloy

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…7a and b, which look very different from what is typically observed for Ni-Ti SMAs, can only be appreciated when one considers the effect of the formation, dissolution and re-precipitation of x-phase [41,[43][44][45]. The smaller irregular peak 3 which follows represents the transformation from austenite to martensite, hampered by the formation of the x-phase which forms quickly [30,32,34]. From the experiment shown in Fig.…”
Section: Dsc Chartsmentioning
confidence: 89%
See 4 more Smart Citations
“…7a and b, which look very different from what is typically observed for Ni-Ti SMAs, can only be appreciated when one considers the effect of the formation, dissolution and re-precipitation of x-phase [41,[43][44][45]. The smaller irregular peak 3 which follows represents the transformation from austenite to martensite, hampered by the formation of the x-phase which forms quickly [30,32,34]. From the experiment shown in Fig.…”
Section: Dsc Chartsmentioning
confidence: 89%
“…x-Phase Formation Materials research on the Ti-Ta system has shown that the formation of x-phase represents the main cause for functional degradation as it impedes the formation of martensite, e.g. [11,21,30,32]. The x-phase quickly forms at Fig.…”
Section: Discussion Spring Processing and Testingmentioning
confidence: 99%
See 3 more Smart Citations